Regulation of heterotrimeric G-protein signaling by NDPK/NME proteins and caveolins: an update - Abu-Taha, Issam H.; Heijman, Jordi; Feng, Yuxi; Vettel, Christiane; Dobrev, Dobromir; Wieland, Thomas (Laboratory investigation, 2018)
Heterotrimeric G proteins are pivotal mediators of cellular signal transduction in eukaryotic cells and abnormal G-protein signaling plays an important role in numerous diseases. During the last two decades it has become evident that the activation status of heterotrimeric G proteins is both highly localized and strongly regulated by a number of factors, including a receptor-independent activation pathway of heterotrimeric G proteins that does not involve the classical GDP/GTP exchange and relies on nucleoside diphosphate kinases (NDPKs). NDPKs are NTP/NDP transphosphorylases encoded by the nme/nm23 genes that are involved in a variety of cellular events such as proliferation, migration, and apoptosis. They therefore contribute, for example, to tumor metastasis, angiogenesis, retinopathy, and heart failure. Interestingly, NDPKs are translocated and/or upregulated in human heart failure. Here we describe recent advances in the current understanding of NDPK functions and how they have an impact on local regulation of G-protein signaling.